The Role of D-Dimers in the Initial Evaluation of COVID-19 [Response To Letter] - Baroiu L; Lese AC; Stefanopol IA; Iancu A; Dumitru C; Ciubara AB; Bujoreanu FC; Baroiu N; Ciubara A; Nechifor A; Anghel L; Tatu AL (Dove Medical Press, 2022)
Liliana Baroiu,1,* Ana Cristina Lese,2 Ioana Anca Stefanopol,3,* Alina Iancu,3,4,* Caterina Dumitru,4,5,* Alexandru Bogdan Ciubara,3,* Florin Ciprian Bujoreanu,6 Nicusor Baroiu,7,* Anamaria Ciubara,1,* Alexandru Nechifor,1,4,* Lucretia Anghel,1,* Alin Laurentiu Tatu1,4,6 1Clinical Medical Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 2Faculty of Visual Arts and Design, “George Enescu” National University of Arts, Iasi, Romania; 3Departament of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 4Multidisciplinary Integrated Center of Dermatological Interface Research Center (MICDIR), “Dunărea de Jos” University, Galați, Romania; 5Pharmaceutical Sciences Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 6Dermatology Departament, “Sf. Parascheva” Infectious Diseases Clinical Hospital, Galati, Romania; 7Manufacturing Engineering Department, Faculty of Engineering, “Dunărea de Jos” University, Galati, Romania*These authors contributed equally to this workCorrespondence: Ana Cristina Lese, Faculty of Visual Arts and Design, “George Enescu” National University of Arts, No. 29, str. Cuza Voda, Iasi, 700040, Romania, Tel +40232212549, Fax +40232212551, Email analese2000@yahoo.com Florin Ciprian Bujoreanu, “Sf. Parascheva” Infectious Diseases Clinical Hospital, No. 343, str. Traian, Galati, 800179, Romania, Tel +40236334477, Fax +40236467752, Email florin.bujoreanu@gmail.com View the original paper by Dr Baroiu and colleagues This is in response to the Letter to the Editor